Itraconazole-loaded micelles based on linear-dendritic poly (ethylene glycol)-b-poly (ε-caprolactone). Issue 18 (12th December 2018) - Li, Shida; Wei, Wenxiu; Jia, Weiping; Zhao, Lechen; Xu, Hongmei; Zhou, Feilong; Zhu, Li; Song, Zhimei; Feng, Sijia; Feng, Runliang
Abstract: A copolymeric micelle formulation of itraconazole (ITR-M) was prepared using linear-dendritic monoallyloxy poly (ethylene glycol)-b-poly (ε-caprolactone) (APEG-PCL) as drug carrier materials. DL and EE values of ITR-M were 5.70 ± 0.12% and 91.30 ± 1.90%, respectively. The micelle formulation enhanced the ITR solubility up to 30.42 μg/mL. In vitro release of ITR from the ITR-M was mainly drug diffusion process followed by the copolymer's degradation. ITR-M showed similar anti- Candida albicans activity to that of crude ITR although its release of ITR was slow and continuous. The in vivo pharmacokinetic study demonstrated that the ITR-M could improve tissue distribution of ITR. In conclusion, APEG-PCL could be a potential carrier in the development of antifungal drug delivery system.